The impact of an integrated medical leadership programme. Issue 1 (16th March 2015) - Agius, Steven J.; Brockbank, Amy; Baron, Rebecca; Farook, Saleem; Hayden, Jacky
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to determine the impact of an integrated Medical Leadership Programme (MLP) on a cohort of participating specialty doctors and the NHS services with which they were engaged. Design/methodology/approach – This was a qualitative study designed to obtain rich textual data on a novel training intervention. Semi-structured interviews were conducted with participating MLP trainees at fixed points throughout the programme in order to capture their experiences. Resulting data were triangulated with data from extant documentation, including trainees' progress reports and summaries of achievements. Recurring discourses and themes were identified using a framework thematic analysis. Findings – Evidence of the positive impact upon trainees and NHS services was identified, along with challenges. Evidence of impact across all the domains within the national Medical Leadership Competency Framework was also identified, including demonstrating personal qualities, working with others, managing services, improving services and setting direction. Research limitations/implications – Data were drawn from interviews with a small population of trainees undertaking a pilot MLP in a single deanery, so there are inevitable limitations for generalisability in the quantitative sense. Whilst the pilot trainees were a self-selected group, it was a group of mixed origin and ability. Practical implications – The study has provided valuable lessons for the design of future leadership programmes aimed at doctors in training. Originality/value – Identifying the effectiveness of an innovative model of delivery with regard to the Medical Leadership Curriculum may assist with medical staff engagement and support health service improvements to benefit patient care.